Use of E-Commerce in The World of Business - Zulkarnain Kedah (Pandawan Sejahtera Indonesia, 2023)
The process of purchasing, offering for sale, or transferring goods, services, and information over computer networks is known as electronic commerce (e-commerce). E-commerce is a subset of e-business, which has a broader definition that includes business partners, customer support, and job openings in addition to commercial activities. A database or database (database), e-mail or electronic mail (e-mail), non-computer technology in the form of different delivery systems, and a method of payment for e-commerce are additional requirements for e-commerce in addition to networking technologies. Given that e-commerce is electronic, customers can access and place orders from many locations. Given the current state of modern technology, a client wishing to access online shopping need not physically be there, as there are numerous locations in Indonesia's major cities that offer Wi-Fi-enabled internet access via laptop, notebook, or Personal Digital Assistant (PDA). So, this is a crucial time for businesses to establish e-commerce services. E-commerce is still largely unused in Indonesia. Following some background information, the author talks about the benefits of e-commerce to his business goals.